An injectable thermosensitive hydrogel loaded with a theranostic nanoprobe for synergistic chemo–photothermal therapy for multidrug-resistant hepatocellular carcinoma. Issue 15 (22nd March 2022) - Huang, Shanzhou; Ma, Zuyi; Sun, Chengjun; Zhou, Qi; Li, Zhenchong; Wang, Shujie; Yan, Qian; Liu, Chunsheng; Hou, Baohua; Zhang, Chuanzhao
Abstract : An on-demand sustained-release platform was constructed for synergistic chemo–photothermal therapy of multi-drug resistance (MDR) hepatocellular carcinoma (HCC), by using an injectable thermosensitive hydrogel loaded with a theranostic nanoprobe. Abstract : Multi-drug resistance (MDR) is a complicated cellular defense mechanism for tumor cells to resist chemotherapy drugs, which is also the main cause of chemotherapy failure. In this study, a local injectable hydrogel delivery system was used to construct an on-demand sustained-release platform with the advantages of chemotherapy, photothermal therapy (PTT), and magnetic resonance imaging (MRI). It could achieve synergistic chemo–photothermal therapy and real-time evaluation of the therapeutic effects ( via MRI) for MDR hepatocellular carcinoma (HCC). Furthermore, after a single administration, the prepared hydrogel with a theranostic nanoprobe could release the therapeutic agents on demand for up to 14 d. Firstly, doxorubicin (DOX) and gold-manganese oxide (Au–MnO) nanoparticles (NPs) were incorporated into liposome-based self-assembled micelles, then loaded into the thermosensitive hydrogel (F127) to form DOX@Au-MnO-L NPs/F127 hydrogel (DAML/H). The prepared NP complex showed a spherical morphology with a narrow size distribution. The prepared hydrogel drug delivery system had injectable properties and stable photothermal conversion. Both the DOX@Au–MnO–L NPs and DAML/H showed controlled drug release under near infrared (NIR) laser irradiation. The in vitro MRI studies indicated that the prepared DAML/H had a high relaxation rate (14.38 mM −1 s −1 ) and good MRI scanning sensitivity conditions. The in vitro and in vivo results suggested the synergistic chemo–photothermal therapy of DAML/H with NIR irradiation (808 nm, 1 W cm −2, 10 min) improved the antitumor efficacy for MDR HCC. The in vivo retention experiment of Au in tumors indicated that the prepared hydrogel drug delivery system (DAML/H) had a good ability to retain Au in the tumor for a long time (at least 14 d). The western blotting results revealed that DAML/H with laser treatment could effectively downregulate P-glycoprotein (P-gp), p53 and antiapoptotic protein (Bcl-2), whereas the expression level of proapoptotic protein (Bax) and caspase-3 were increased. Therefore, DAML/H could serve as a promising synergistic chemo–photothermal therapy for MDR HCC, and a single administration might achieve long-term (14 d), on-demand, sustained-release treatment of tumors.